Differential patterns of cortical activation as a function of fluid reasoning complexity - Perfetti, Bernardo; Saggino, Aristide; Ferretti, Antonio; Caulo, Massimo; Romani, Gian Luca; Onofrj, Marco (Human brain mapping, 2009)
Fluid intelligence (gf) refers to reasoning and problem solving abilities. It is considered a human higher cognitive factor central to general intelligence (g). The regions of the cortex supporting gf have been revealed by recent bioimaging studies and valuable hypothesis on the neural correlates of individual differences have been proposed. However, little is known about the interaction between individual variability in gf and variation in cortical activity following task complexity increase. To further investigate this, two samples of participants (high‐IQ, N = 8; low‐IQ, N = 10) with significant differences in gf underwent two reasoning (moderate and complex) tasks and a control task adapted from the Raven progressive matrices. Functional magnetic resonance was used and the recorded signal analyzed between and within the groups. The present study revealed two opposite patterns of neural activity variation which were probably a reflection of the overall differences in cognitive resource modulation: when complexity increased, high‐IQ subjects showed a signal enhancement in some frontal and parietal regions, whereas low‐IQ subjects revealed a decreased activity in the same areas. Moreover, a direct comparison between the groups' activation patterns revealed a greater neural activity in the low‐IQ sample when conducting moderate task, with a strong involvement of medial and lateral frontal regions thus suggesting that the recruitment of executive functioning might be different between the groups. This study provides evidence for neural differences in facing reasoning complexity among subjects with different gf level that are mediated by specific patterns of activation of the underlying fronto‐parietal network. Hum Brain Mapp, 2009. © 2007 Wiley‐Liss, Inc.